Teaching and learning in ecology: a horizon scan of emerging challenges and solutions. Issue 1 (8th October 2020) - Cooke, Julia; Araya, Yoseph; Bacon, Karen L.; Bagniewska, Joanna M.; Batty, Lesley C.; Bishop, Tom R.; Burns, Moya; Charalambous, Magda; Daversa, David R.; Dougherty, Liam R.; Dyson, Miranda; Fisher, Adam M.; et al.
Abstract : We currently face significant, anthropogenic, global environmental challenges and the role of ecologists in mitigating these challenges is arguably more important than ever. Consequently there is an urgent need to recruit and train future generations of ecologists, both those whose main area is ecology, but also those involved in the geological, biological and environmental sciences. Here we present the results of a horizon scanning exercise that identified current and future challenges facing the teaching of ecology, through surveys of teachers, students and employers of ecologists. Key challenges identified were grouped in terms of the perspectives of three groups: students, for example the increasing disconnect between people and nature; teachers, for example the challenges associated with teaching the quantitative skills that are inherent to the study of ecology; and society, for example poor societal perceptions of the field of ecology. In addition to the challenges identified, we propose a number of solutions developed at a workshop by a team of ecology teaching experts, with supporting evidence of their potential to address many of the problems raised. These proposed solutions include developing living labs, teaching students to be ecological entrepreneurs and influencers, embedding skills‐based learning and coding in the curriculum, an increased role for learned societies in teaching and learning, and using new technology to enhance fieldwork studies including virtual reality, artificial intelligence and real‐time spoken language translation. Our findings are focused towards UK higher education, but they should be informative for students and teachers of a wide range of educational levels, policy makers and professional ecologists worldwide.